Oral Health as a citizen’s right and its relationship with the prevention of Noncommunicable Diseases - Lorenzo, Susana (2022)
The right to health in Uruguay is enshrined in the Constitution of the Republic and law 18211 of the National Integrated Health System (SNIS). However, the health of young people between 15 and 24 years old is a worrying issue. The most prevalent oral pathologies share some common characteristics with noncommunicable diseases (NCDs); they can be addressed jointly and efficiently through a common risk approach. The right to health can be approached from the pedagogy of the oppressed. This approach proposes a critical and problematizing perspective using theatrical tools and exercises to play with where the protagonists participate as spectators-actors.The objectives of this work were to develop a learning-teaching process on oral health and its relationship with NCDs with high school students and teachers in the cities of Rocha and La Paloma, Uruguay, and to describe the oral health situation of the young people involved.The experience was developed between October and November 2017, combining exhibition activities and workshops, working from the pedagogy of the oppressed and hope, and performing activities of image theater and forum theater. Oral health was surveyed in terms of caries and paradenciopathies (WHO Methodology, 1997), and a socio-demographic survey was administered. The students worked as health promoters participating in student fairs, sharing the contents addressed with students from the other levels of the high school. They finished the process with the drafting of a letter addressed to the local health authorities, where they expressed their concerns and demands for the right to oral health and the need for comprehensive dental care.When comparing the data collected with the national data for young people in the provinces, the caries situation was better than at the national level. The frequency of smoking was lower than expected.At the end of the project, the high school students could complete the work process by acquiring knowledge of oral health and advocating for the right to health.